SAFETY AND DISPOSAL PROBLEMS OF FLUORESCENT LAMPS - Kobyakov, Sergey (SWorld-Ger Conference proceedings, 2023)
The work considers the issue of the danger of fluorescent lamps in case of their damage and the problem of disposal. The characteristics of the lamps and the safety measures that must be taken if the lamp is broken are given. The state of production facil